Critical Current and Pinning Features of a CaKFe4As4 Polycrystalline Sample - Armando Galluzzi (MDPI AG, 2021)
We analyze the magnetic behavior of a CaKFe4As4 polycrystalline sample fabricated by a mechanochemically assisted synthesis route. By means of DC magnetization (M) measurements as a function of the temperature (T) and DC magnetic field (H) we study its critical parameters and pinning features. The critical temperature Tc has been evaluated by M(T) curves performed in Zero Field Cooling-Field Cooling conditions. These curves show the presence of a little magnetic background for temperatures above Tc, as also confirmed by the hysteresis loops M(H). Starting from the M(H) curves, the critical current density Jc of the sample has been calculated as a function of the field at different temperatures in the framework of the Bean critical state model. The Jc(H) values are in line with the ones reported in the literature for this typology of samples. By analyzing the temperature dependence of the critical current density Jc(T) at different magnetic fields, it has been found that the sample is characterized by a strong type pinning regime. This sample peculiarity can open perspectives for future improvement in the fabrication of this material.